Cellular Senescence in Cardiovascular Diseases: From Pathogenesis to Therapeutic Challenges - Dan Li; Yongnan Li; Hong Ding; Yuqin Wang; Yafei Xie; Xiaowei Zhang (Journal of Cardiovascular Development and Disease, 2023)
Cellular senescence (CS), classically considered a stable cell cycle withdrawal, is hallmarked by a progressive decrease in cell growth, differentiation, and biological activities. Senescent cells (SNCs) display a complicated senescence-associated secretory phenotype (SASP), encompassing a variety of pro-inflammatory factors that exert influence on the biology of both the cell and surrounding tissue. Among global mortality causes, cardiovascular diseases (CVDs) stand out, significantly impacting the living quality and functional abilities of patients. Recent data suggest the accumulation of SNCs in aged or diseased cardiovascular systems, suggesting their potential role in impairing cardiovascular function. CS operates as a double-edged sword: while it can stimulate the restoration of organs under physiological conditions, it can also participate in organ and tissue dysfunction and pave the way for multiple chronic diseases under pathological states. This review explores the mechanisms that underlie CS and delves into the distinctive features that characterize SNCs. Furthermore, we describe the involvement of SNCs in the progression of CVDs. Finally, the study provides a summary of emerging interventions that either promote or suppress senescence and discusses their therapeutic potential in CVDs.